Middle to late Holocene chironomid-inferred July temperatures for the central Northwest Territories, Canada. - Upiter, Lindsay M.; Vermaire, Jesse C.; Patterson, R. Timothy; Crann, Carley A.; Galloway, Jennifer M.; Macumber, Andrew L.; Neville, Lisa A.; Swindles, Graeme T.; Falck, Hendrik; Roe, Helen M.; Pisaric, Michael F. J. (Journal of Paleolimnology, 2014)
We analyzed subfossil chironomids, sediment organic matter and sediment particle size data from a 1.11-m-long freeze core collected from Carleton Lake (unofficial name), located approximately 120 km north of the modern treeline. This well-dated core spans the last ca. 6,500 years. Two chironomid transfer functions were applied to infer mean July air temperatures. Our results indicated that the chironomid-inferred temperatures from this lake sediment record did not pass a significance test, suggesting that other factors in addition to temperature may have been important in structuring the chironomid community through time. Although not statistically significant, the chironomid-inferred temperatures from this site do follow a familiar pattern, with highest inferred temperatures occurring during the Holocene Thermal Maximum (~6–4 cal kyr BP), followed by a long-term cooling trend, which is reversed during the last 600 years. The largest change in the chironomid assemblage, which occurred between ca. 4,600 and 3,900 cal yr BP is possibly related to the well-documented northward advance and subsequent retreat of treeline in this region.